﻿UHPLC-Orbitrap screening of oleraindoles in hydromethanolic extracts of Portulaca oleracea - Yulian Voynikov; Reneta Gevrenova; Dimitrina Zheleva-Dimitrova; Vessela Balabanova; Irina Nikolova; Lyubomir Marinov; Iossif Benbassat; Georgi Momekov (Pensoft Publishers, 2023)
Purslane (Portulaca oleracea L., Portulacaceae) is a widespread edible plant with significant ethnobotanical and ethnopharmacological importance. The plant is characteristic for the presence of a class of indoline amide glucoside alkaloids, called cyclo-dopa amides, or oleraceins. Additionally, a new, structurally similar to oleraceins, class of indole amides have been discovered recently, called oleraindoles. These compounds have been evaluated to possess antiinflammatory and anticholinesterase activities. Herein, utilizing UHPLC-Orbitrap-MS with MS2 filtering by diagnostic ion filtering (DIF), and diagnostic difference filtering (DDF) using different data analysis tools, eight compounds with oleraindole structure were tentatively identified.